Self-supporting cobaltosic oxide composite electrode, preparation method thereof and application of self-supporting cobaltosic oxide composite electrode in seawater electrolysis
By combining the cobalt-based coordination polymer with activated carbon fiber paper and using melamine formaldehyde-polyethyleneimine resin as the binder, a composite electrode from supporting tricobalt tetroxide was prepared, which solved the problem of insufficient stability and anti-interference of electrocatalyst in seawater electrolysis, and achieved efficient seawater hydrogen production and oxygen production reaction.
Patent Information
- Application Number
- CN202411812085.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
In seawater electrolysis, existing electrocatalysts are difficult to effectively apply due to low seawater conductivity, precipitation of calcium and magnesium ion and chloride ion corrosion.
The cobalt-based coordination polymer was combined with activated carbon fiber paper by using melamine formaldehyde-polyethyleneimine resin as the binder, and a composite electrode supported by tricobalt tetroxide was prepared after high-temperature annealing. This electrode improves conductivity and electrocatalytic performance through a nitrogen-doped carbon layer, protects electrocatalytic active components, and reduces ionic interference in seawater.
It achieves high catalytic activity, low overpotential, high stability and anti-interference in alkaline seawater, can maintain high current density for a long time, and is suitable for seawater hydrogen production and oxygen production reactions.
Smart Images

Figure HDA0005180783710000011 
Figure HDA0005180783710000012 
Figure HDA0005180783710000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a self-supporting cobalt oxide composite electrode and a preparation method thereof and application thereof in seawater electrolysis. Background Art
[0002] With the depletion of traditional fossil energy and the intensification of the greenhouse effect, people are looking for low-cost, environmentally friendly clean energy. Hydrogen energy, as the most promising clean energy in the 21st century, can be produced through methods such as fossil fuel refining, methane recombination, photocatalytic water splitting, and water electrolysis. Seawater is one of the most abundant natural water sources on Earth, accounting for 96.5% of the world's total water resources. Therefore, water electrolysis is generally considered to be the most promising carbon-free and efficient hydrogen production strategy.
[0003] Generally speaking, water electrolysis includes two half reactions, namely the anode oxygen evolution reaction (OER) and the cathode hydrogen evolution reaction (HER). Both reactions require effective electrocatalysts to reduce energy consumption. Although commercial precious metal catalysts have high activity, their high price and scarce reserves in the earth's crust limit their practical applications. Therefore, researchers have turned their attention to the research and development of non-precious metal electrocatalysts.
[0004] However, in actual research and development, hydrogen production from seawater is still very challenging due to the low conductivity of seawater itself, the calcium and magnesium ions in it easily become precipitates and inactivate the active sites, and the high concentration of chloride ions will corrode the electrodes. Therefore, it is urgent to develop a catalytic electrode with high catalytic activity, low overpotential, high stability, and no interference from chloride ions and other plasmas in seawater. Summary of the invention
[0005] The purpose of the present invention is to provide a self-supporting cobalt oxide composite electrode and a preparation method thereof and application in seawater electrolysis. The composite electrode has the properties of high catalytic activity, low overpotential, high stability, and no interference from chloride ions in seawater, and can be used for hydrogen and oxygen production reactions in alkaline seawater.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A self-supporting cobalt oxide composite electrode, using melamine formaldehyde-polyethyleneimine resin as a binder, combining a cobalt-based coordination polymer with activated carbon fiber paper, and annealing at high temperature to obtain a composite electrode. The activated carbon fiber paper is obtained by activating carbon fiber paper to improve hydrophilicity.
[0008] In this scheme, the melamine formaldehyde-polyethyleneimine resin is annealed at high temperature to form a nitrogen-doped carbon layer, which has good electrical conductivity and certain electrocatalytic performance, effectively solving the problem of low electrical conductivity of seawater itself. At the same time, the carbon layer can also protect the electrocatalytic active components wrapped therein, reduce the corrosion of chloride ions in seawater to the electrode, and slow down the precipitation of calcium and magnesium ions on the electrode surface. Compared with the electrode material prepared by the traditional in-situ growth method, the electrode prepared by the present invention has better stability and anti-interference ability and longer service life.
[0009] The self-supporting cobalt tetroxide composite electrode provided by the present invention can solve the problems encountered when using seawater as an electrolyte, such as being free from interference from chloride ions and other plasmas in seawater, and at the same time has high catalytic activity, low overpotential, and high stability, and can be widely used in alkaline seawater hydrogen production and oxygen production reactions.
[0010] In addition, to achieve the above object, the present invention also provides a method for preparing a self-supporting cobalt oxide composite electrode, comprising the following steps:
[0011] S1. Preparation of raw materials:
[0012] Preparation of activated carbon fiber paper: firstly, the carbon fiber paper is mixed with HNO3 solution and dried; then, it is washed, mixed with NaOH solution and dried; finally, it is taken out, washed, and dried to obtain CP, i.e., activated carbon fiber paper;
[0013] Synthesis of melamine formaldehyde-polyethyleneimine resin: melamine, deionized water and formaldehyde are mixed and stirred until clear to obtain oligomeric melamine-formaldehyde resin; then the oligomeric melamine-formaldehyde resin is mixed with polyethyleneimine and fully ground to obtain MP, i.e. melamine formaldehyde-polyethyleneimine resin;
[0014] Synthesis of ZIF-67 nanoparticles: first, cobalt nitrate is added to methanol and fully dissolved, which is recorded as liquid A; 2-methylimidazole is added to methanol and fully dissolved, which is recorded as liquid B; then liquid B is poured into liquid A, and after fully stirring, centrifugation, washing, and drying are performed in sequence to obtain ZIF-67 nanoparticles, i.e., cobalt-based coordination polymer particles;
[0015] S2. Preparation of composite electrode:
[0016] S21. Weigh a certain amount of ZIF-67 nanoparticles and melamine formaldehyde-polyethyleneimine resin, mix them thoroughly, and then apply them to the surface of activated carbon fiber paper. After drying, apply the reverse side in the same way to obtain ZIF-67 / MP / CP after drying.
[0017] S22. Place ZIF-67 / MP / CP in a tubular furnace, raise the temperature to 500-900°C in an inert gas atmosphere, keep it at this temperature for 2 hours, and then cool it down naturally to obtain ZIF-67 / MP / CP-T, i.e., a composite electrode.
[0018] The preparation method provided by the invention has the advantages of simplicity, high repeatability and low cost.
[0019] Preferably, in the preparation of activated carbon fiber paper in step S1, the temperatures of the first two dryings are both 92-98° C., and the drying time is both 10-15 hours.
[0020] Preferably, in the synthesis of melamine formaldehyde-polyethyleneimine resin in step S1, the mass ratio of the oligomeric melamine-formaldehyde resin to the polyethyleneimine is 1:(0.2-2).
[0021] Preferably, in the synthesis of ZIF-67 nanoparticles in step S1, the mass ratio of cobalt nitrate to 2-methylimidazole is (0.1-1): (0.1-1).
[0022] Preferably, in step S21, the mass ratio of ZIF-67 to melamine formaldehyde-polyethyleneimine resin is (1-30):100.
[0023] Preferably, in step S22, the heating rate is 2-10°C / min.
[0024] In addition, to achieve the above-mentioned purpose, the present invention also provides an application of a self-supporting cobalt tetroxide composite electrode in seawater electrolysis.
[0025] The composite electrode prepared by the present invention can be directly used as the cathode and anode of an electrolytic cell to produce hydrogen and oxygen by electrolyzing water.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention uses melamine formaldehyde-polyethyleneimine resin as an adhesive, combines a cobalt-based coordination polymer with activated carbon fiber paper, and obtains a composite electrode after high-temperature annealing. In the electrode, the melamine formaldehyde-polyethyleneimine resin forms a nitrogen-doped carbon layer after high-temperature annealing, which has good electrical conductivity and certain electrocatalytic performance, effectively solving the problem of low electrical conductivity of seawater itself. At the same time, the carbon layer can also protect the electrocatalytic active components wrapped therein, reduce the corrosion of chloride ions in seawater to the electrode, and slow down the precipitation of calcium and magnesium ions on the electrode surface. Compared with the electrode material prepared by the traditional in-situ growth method, the electrode prepared by the present invention has better stability and anti-interference ability and longer service life.
[0028] 2. The self-supporting cobalt oxide composite electrode provided by the present invention has good dual catalytic function in the hydrogen evolution reaction and oxygen evolution reaction of water electrolysis, which can simplify the reaction system design and reduce the catalyst synthesis cost, and realize more efficient, sustainable and economical energy conversion; at the same time, it has good catalytic stability and long service life, and can maintain high and long-term stable operation at high current density. For example, in alkaline seawater, it can run continuously for more than 13 hours and can maintain industrial-grade current density (500mA / cm 2 ).
[0029] 3. In the self-supporting cobalt tetroxide composite electrode provided by the present invention, the current density generated under the same overpotential of cobalt tetroxide catalytic activity is higher, and the current density can reach up to 800mA / cm 2 .
[0030] 4. The self-supporting cobalt tetroxide composite electrode provided by the present invention has good anti-interference performance and can be used in the hydrogen production and oxygen production reaction processes of alkaline seawater without being interfered with or affected by the presence of various ions such as chloride ions in seawater.
[0031] 5. The self-supporting cobalt oxide composite electrode provided by the present invention is an integrated composite electrode material. Based on its high specific surface area and good conductivity, the material has high catalytic activity, strong stability, anti-interference and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 : SEM images of activated carbon fiber paper, ZIF-67, ZIF-67 / MP / CP and ZIF-67 / MP / CP-T;
[0033] in, Figure 1 a in the figure is a scanning electron microscope image of carbon fiber paper; Figure 1 b is the scanning electron microscope image of ZIF-67; Figure 1 c in the figure is the scanning electron microscope image of ZIF-67 / MP / CP; Figure 1 d, e, f, g, and h are SEM images of ZIF-67 / MP / CP-T (T is 500°C, 600°C, 700°C, 800°C, and 900°C, respectively);
[0034] Figure 2 : LSV curves of HER and OER of ZIF-67 / MP / CP-700 composite electrode materials in seawater at pH = 14;
[0035] Figure 3 : LSV curves of HER and OER of ZIF-67 / MP / CP-800 composite electrode materials in seawater at pH = 14;
[0036] Figure 4: LSV curves of HER and OER of ZIF-67 / MP / CP-900 composite electrode materials in seawater at pH = 14;
[0037] Figure 5 :ZIF-67 / MP / CP-800 in seawater with pH=14 at 500mA / cm -2 The IT test is carried out at a potential corresponding to the current density. DETAILED DESCRIPTION
[0038] Example 1
[0039] S1. Preparation of raw materials.
[0040] Cut the carbon fiber paper into 1cm×2cm size, mix it with 50mL 1mol / L HNO3, and place it in a 95℃ oven to react for 12 hours. Take it out and wash it with deionized water until it is neutral, then mix it with 50mL 1mol / L NaOH, and place it in a 95℃ oven to react for 12 hours. Take it out and wash it with deionized water until it is neutral, and dry it to obtain activated carbon fiber paper.
[0041] 1.455 g of cobalt nitrate was dissolved in 50 mL of methanol and stirred thoroughly until dissolved, which was recorded as liquid A; 1.6446 g of 2-methylimidazole was dissolved in 50 mL of methanol and stirred thoroughly until dissolved, which was recorded as liquid B. Liquid B was poured into liquid A and stirred at medium speed for 1 hour. After the reaction was completed, the mixture was separated by centrifugation at 9000 rpm for 3 minutes, washed three times with methanol, and dried in an oven at 75°C to obtain ZIF-67 nanoparticles.
[0042] 3.0 g of melamine, 5.4 mL of deionized water, and 6.9 mL of formaldehyde were mixed and stirred in a water bath at 80° C. using a magnetic stirrer until the mixture was clear to obtain an oligomeric melamine-formaldehyde resin. The obtained oligomeric melamine-formaldehyde resin was mixed with polyethyleneimine at a mass ratio of 1:1 and fully ground to obtain a melamine formaldehyde-polyethyleneimine resin.
[0043] S2. Preparation of composite electrodes.
[0044] Weigh 10 mg of ZIF-67 and mix it with MP at a mass ratio of 1:5. After mixing evenly, apply it to the surface of activated carbon fiber paper, place it in an oven for drying, and apply it to the reverse side in the same way. After drying, ZIF-67 / MP / CP is obtained. ZIF-67 / MP / CP is placed in a tubular furnace, maintained in an inert gas atmosphere, and heated to 700°C at a heating rate of 5°C / min. After keeping warm for 2 hours, the temperature is naturally lowered to obtain ZIF-67 / MP / CP-700.
[0045] The scanning electron microscope images of the activated carbon fiber paper, ZIF-67, ZIF-67 / MP / CP and ZIF-67 / MP / CP-T in Example 1 are as follows: Figure 1 shown.
[0046] in, Figure 1 a in the figure is a scanning electron microscope image of carbon fiber paper;
[0047] Figure 1 b in the figure is the synthesized ZIF-67 nanoparticles, and the image shows that the particles are polyhedral in morphology and have a particle size of 200-800nm;
[0048] Figure 1 c in the figure is the scanning electron microscope image of ZIF-67 / MP / CP. Figure 1 As can be observed in c, ZIF-67 / MP / CP is prepared by mixing ZIF-67 nanoparticles into melamine formaldehyde-polyethyleneimine resin, coating it on carbon fiber paper and curing it. The ZIF-67 nanoparticles are evenly dispersed in the melamine formaldehyde-polyethyleneimine resin cured layer, and the resin cured layer is firmly bonded to the carbon fiber paper.
[0049] Figure 1 dh in FIG is a scanning electron microscope image of ZIF-67 / MP / CP-T. In addition to the above annealing treatment at 700°C, ZIF-67 / MP / CP was also annealed at 500, 600, 800, and 900°C in a nitrogen atmosphere. Figure 1 It can be seen from the dh that the melamine formaldehyde-polyethyleneimine resin was successfully converted into a black nitrogen-doped carbon layer and firmly loaded on the carbon fiber paper. Cobalt tetroxide nanoparticles were observed on the surface of the composite electrode. From the cross-section of the carbon layer, polyhedral carbon particles transformed from ZIF-67 were seen, with a particle size of about 200-800nm.
[0050] In order to test the electrocatalytic performance of ZIF-67 / MP / CP-700 composite electrode materials in alkaline seawater environment, electrochemical tests were carried out in alkaline seawater with pH = 14, such as Figure 2 As shown in the HER test, ZIF-67 / MP / CP-700 has ηHER@10mA / cm 2 =0.061V,ηHER@50mA / cm 2 =0.266V,ηHER@100mA / cm 2 =0.336V,ηHER@500mA / cm 2 =0.636V performance; in OER test, ZIF-67 / MP / CP-700 has ηOER@10mA / cm 2 =0.054V,ηOER@50mA / cm2 =0.181V,ηOER@100mA / cm 2 =0.273V,ηOER@300mA / cm 2 =0.447V performance.
[0051] In summary, ZIF-67 / MP / CP-700 can effectively catalyze hydrogen and oxygen evolution reactions in alkaline seawater (pH = 14), with the HER current density reaching up to 700 mA / cm 2 , the OER current density can reach up to 300mA / cm 2 .
[0052] Example 2
[0053] S1. Preparation of raw materials.
[0054] Cut the carbon fiber paper into 1cm×2cm size, mix it with 50mL 1mol / L HNO3, and place it in a 95℃ oven to react for 12 hours. Take it out and wash it with deionized water until it is neutral, mix it with 50mL 1mol / L NaOH, and place it in a 95℃ oven to react for 12 hours. Take it out and wash it with deionized water until it is neutral, and dry it to obtain activated carbon fiber paper.
[0055] 1.455 g of cobalt nitrate was dissolved in 50 mL of methanol and stirred thoroughly until dissolved, which was recorded as liquid A; 1.6446 g of 2-methylimidazole was dissolved in 50 mL of methanol and stirred thoroughly until dissolved, which was recorded as liquid B. Liquid B was poured into liquid A and stirred at medium speed for 1 hour. After the reaction was completed, the mixture was separated by centrifugation at 9000 rpm for 3 minutes, washed three times with methanol, and dried in an oven at 75°C to obtain ZIF-67 nanoparticles.
[0056] 3.0 g of melamine, 5.4 mL of deionized water, and 6.9 mL of formaldehyde were mixed and stirred in a water bath at 80° C. using a magnetic stirrer until the mixture was clear to obtain an oligomeric melamine-formaldehyde resin. The obtained oligomeric melamine-formaldehyde resin was mixed with polyethyleneimine at a mass ratio of 1:1 and fully ground to obtain a melamine formaldehyde-polyethyleneimine resin.
[0057] S2. Preparation of composite electrodes.
[0058] Weigh 10 mg of ZIF-67 and mix it with MP at a mass ratio of 1:5. After mixing evenly, apply it to the surface of activated carbon fiber paper, place it in an oven for drying, and apply it to the reverse side in the same way. After drying, ZIF-67 / MP / CP is obtained. ZIF-67 / MP / CP is placed in a tubular furnace, maintained in an inert gas atmosphere, and heated to 800°C at a heating rate of 5°C / min. After keeping warm for 2 hours, the temperature is naturally lowered to obtain ZIF-67 / MP / CP-800.
[0059] In order to test the electrocatalytic performance of ZIF-67 / MP / CP-800 composite electrode materials in alkaline seawater environment, electrochemical tests were carried out in alkaline seawater with pH = 14. Figure 3 As shown in the HER test, ZIF-67 / MP / CP-800 has ηHER@10mA / cm 2 =0.057V,ηHER@50mA / cm 2 =0.220V,ηHER@100mA / cm 2 =0.285V,ηHER@500mA / cm 2 =0.535V performance; in OER test, ZIF-67 / MP / CP-800 has ηOER@10mA / cm 2 =0.076V,ηOER@50mA / cm 2 =0.226V,ηOER@100mA / cm 2 =0.313V,ηOER@300mA / cm 2 =0.464V performance.
[0060] In summary, ZIF-67 / MP / CP-800 can also effectively catalyze hydrogen and oxygen evolution reactions in alkaline seawater (pH = 14), with the HER current density reaching up to 800 mA / cm 2 , the OER current density can reach up to 300mA / cm 2 ; and its catalytic activity for HER is better than that of ZIF-67 / MP / CP-700, and the energy (overpotential) required to achieve the same current density is lower than that of ZIF-67 / MP / CP-700.
[0061] Example 3
[0062] S1. Preparation of raw materials.
[0063] Cut the carbon fiber paper into 1cm×2cm size, mix it with 50mL 1mol / L HNO3, and place it in a 95℃ oven to react for 12 hours. Take it out and wash it with deionized water until it is neutral, mix it with 50mL 1mol / L NaOH, and place it in a 95℃ oven to react for 12 hours. Take it out and wash it with deionized water until it is neutral, and dry it to obtain activated carbon fiber paper.
[0064] 1.455 g of cobalt nitrate was dissolved in 50 mL of methanol and stirred thoroughly until dissolved, which was recorded as liquid A; 1.6446 g of 2-methylimidazole was dissolved in 50 mL of methanol and stirred thoroughly until dissolved, which was recorded as liquid B. Liquid B was poured into liquid A and stirred at medium speed for 1 hour. After the reaction was completed, the mixture was separated by centrifugation at 9000 rpm for 3 minutes, washed three times with methanol, and dried in an oven at 75°C to obtain ZIF-67 nanoparticles.
[0065] 3.0 g of melamine, 5.4 mL of deionized water, and 6.9 mL of formaldehyde were mixed and stirred in a water bath at 80° C. using a magnetic stirrer until the mixture was clear to obtain an oligomeric melamine-formaldehyde resin. The obtained oligomeric melamine-formaldehyde resin was mixed with polyethyleneimine at a mass ratio of 1:1 and fully ground to obtain a melamine formaldehyde-polyethyleneimine resin.
[0066] S2. Preparation of composite electrodes.
[0067] Weigh 10 mg of ZIF-67 and mix it with MP at a mass ratio of 1:5. After mixing evenly, apply it to the surface of activated carbon fiber paper, place it in an oven for drying, and apply it to the reverse side in the same way. After drying, ZIF-67 / MP / CP is obtained. ZIF-67 / MP / CP is placed in a tubular furnace, maintained in an inert gas atmosphere, and heated to 900°C at a heating rate of 5°C / min. After keeping warm for 2 hours, the temperature is naturally lowered to obtain ZIF-67 / MP / CP-900.
[0068] In order to test the electrocatalytic performance of ZIF-67 / MP / CP-900 composite electrode materials in alkaline seawater environment, electrochemical tests were carried out in alkaline seawater with pH = 14. Figure 4 As shown in the HER test, ZIF-67 / MP / CP-800 has ηHER@10mA / cm 2 =0.085V,ηHER@50mA / cm 2 =0.310V,ηHER@100mA / cm 2 =0.373V,ηHER@500mA / cm 2 =0.648V performance; in OER test, ZIF-67 / MP / CP-800 has ηOER@10mA / cm 2 =0.096V,ηOER@50mA / cm 2 =0.252V,ηOER@100mA / cm 2 =0.333V,ηOER@300mA / cm 2 =0.465V performance.
[0069] In summary, ZIF-67 / MP / CP-900 can also effectively catalyze hydrogen and oxygen evolution reactions in alkaline seawater (pH = 14), with the HER current density reaching up to 720 mA / cm 2 , the OER current density can reach up to 300mA / cm 2 .
[0070] Application example: Self-supporting cobalt oxide composite electrode ZIF-67 / MP / CP-800 electrolyzes water to produce hydrogen in alkaline seawater at pH = 14.
[0071] The present invention simulates the real industrial electrolysis water hydrogen production environment, and the composite electrode material ZIF-67 / MP / CP-800, graphite electrode, silver / silver chloride electrode and alkaline seawater with pH=14 form an electrolytic cell system. Figure 5 As shown in Figure 2, when the hydrogen evolution reaction in alkaline seawater electrolysis is driven by a constant voltage, ZIF-67 / MP / CP-800 can maintain 500 mA / cm -2 The current density output of the commercial platinum-carbon catalyst (Pt / C) decays to 300mA / cm after 2 hours of continuous operation. -2 This result shows that the composite electrode material ZIF-67 / MP / CP-800 exhibits good stability and anti-interference ability, and the catalytic performance is not affected.
Claims
1. A self-supporting cobalt oxide composite electrode, characterized in that: Using melamine formaldehyde-polyethyleneimine resin as a binder, the cobalt-based coordination polymer and activated carbon fiber paper were combined together, and a composite electrode was obtained after high-temperature annealing.
2. The method for preparing a self-supporting cobalt oxide composite electrode according to claim 1, characterized in that: The steps include: S1. Preparation of raw materials: Preparation of activated carbon fiber paper: firstly, the carbon fiber paper is mixed with HNO3 solution and dried; then, it is washed, mixed with NaOH solution and dried; finally, it is taken out, washed, and dried to obtain CP, i.e., activated carbon fiber paper; Synthesis of melamine formaldehyde-polyethyleneimine resin: melamine, deionized water and formaldehyde are mixed and stirred until clear to obtain oligomeric melamine-formaldehyde resin; then the oligomeric melamine-formaldehyde resin is mixed with polyethyleneimine and fully ground to obtain MP, i.e. melamine formaldehyde-polyethyleneimine resin; Synthesis of ZIF-67 nanoparticles: first, cobalt nitrate is added to methanol and fully dissolved, which is recorded as liquid A; 2-methylimidazole is added to methanol and fully dissolved, which is recorded as liquid B; then liquid B is poured into liquid A, and after fully stirring, centrifugation, washing, and drying are performed in sequence to obtain ZIF-67 nanoparticles, i.e., cobalt-based coordination polymer particles; S2. Preparation of composite electrode: S21. Weigh a certain amount of ZIF-67 nanoparticles and melamine formaldehyde-polyethyleneimine resin, mix them thoroughly, and then apply them to the surface of activated carbon fiber paper. After drying, apply the reverse side in the same way to obtain ZIF-67 / MP / CP after drying. S22. Place ZIF-67 / MP / CP in a tubular furnace, raise the temperature to 500-900°C in an inert gas atmosphere, keep it at this temperature for 2 hours, and then cool it down naturally to obtain ZIF-67 / MP / CP-T, i.e., a composite electrode.
3. The method for preparing a self-supporting cobalt oxide composite electrode according to claim 2, characterized in that: In the preparation of activated carbon fiber paper in step S1, the temperatures of the first two dryings are both 92-98° C., and the drying time is both 10-15 hours.
4. The method for preparing a self-supporting cobalt oxide composite electrode according to claim 2, characterized in that: In the synthesis of melamine formaldehyde-polyethyleneimine resin in step S1, the mass ratio of oligomeric melamine-formaldehyde resin to polyethyleneimine is 1:(0.2-2).
5. The method for preparing a self-supporting cobalt oxide composite electrode according to claim 2, characterized in that: In the synthesis of step S1 ZIF-67 nanoparticles, the mass ratio of cobalt nitrate and 2-methylimidazole is (0.1-1): (0.1-1).
6. The method for preparing a self-supporting cobalt oxide composite electrode according to claim 2, characterized in that: In step S21, the mass ratio of ZIF-67 to melamine formaldehyde-polyethyleneimine resin is (1-30):
100.
7. The method for preparing a self-supporting cobalt oxide composite electrode according to claim 2, characterized in that: In step S22, the heating rate is 2-10°C / min.
8. The use of the self-supporting cobalt oxide composite electrode in seawater electrolysis according to claim 1, characterized in that: The composite electrode is directly used as cathode or anode of an electrolytic cell.
Citation Information
Patent Citations
Cobaltosic oxide / carbon composite electrode material, manufacturing method and application
CN108198701A
Preparation method for synthesizing melamine resin-based carbon material with ZIF-67 as template and applications
CN109704305A
N, S-doped porous carbon loaded Co composite material and preparation method and application thereof
CN115058731A